Advantages and disadvantages of using the problem-based learning method - PBL for upper level students in business areas - Wendt Mischiatti, João Augusto; Palermo Pupo, Fabricio; Gomes de Menezes, Glauco; Fukumi Tsunoda, Denise; Nunes Silva, Helena de Fátima (International Journal for Innovation Education and Research, 2019)
Problem-based learning (PBL) is a teaching method that encourages the student´s proactivity to reason, in order to seek solutions to the problem in question. This article aims to evaluate the advantages and disadvantages of using the PBL method for top level students in business areas. In order to meet the objective, a questionnaire was prepared from the literature studied and sent to 375 students, with a return rate of 19%. The main results show that 74% of the respondents consider that the practical classes contribute to the memorization of the content, 93% of the respondents consider it an opportunity for personal and social formation, besides promoting the sharing of knowledge and improvement in decision-making. It also found that 83% feel more protagonists in the PBL method and more than 81% feel more engaged in their own learning. As a result, it was possible to identify a favorable perception of the learning method that leads and engages the student. This research also allows us to conclude that the PBL is, in fact, perceived as a more current and innovative method by students.